Performance Evaluation of Cement Mortars Containing Marble Dust and Glass Fiber Exposed to High Temperature by Using Taguchi Method - Keleştemur, Oğuzhan; Arıcı, Erdinç; Yıldız, Servet; Gökçer, Bihter (My University, 2014)
This paper investigated the effects of marble dust and glass fiber on mechanical and physical properties of cement mortars exposed to high temperature as experimentally and statistically. For this purpose, the mixes containing marble dust (0%, 20%, 40% and 50% by volume) and glass fiber (0 kg/m3 , 0.25 kg/m3 , 0.50 kg/m3 , 0.75 kg/m3 ) were prepared. The compressive strength and porosity value of the cement mortars were determined after being exposed to high temperatures (400, 600 and 800 C). In order to reduce the numbers of experiments, an L16 (43 ) Taguchi orthogonal array was adopted to the study. Percentage of marble dust, amount of glass fiber and degree of temperature were changed to explore their effects on the compressive strength and porosity values of specimens. Statistically effects of the factors were also determined by using analysis of variance (ANOVA) method. Finally, experimental findings were compared with statistical results and a good agreement between them was achieved.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Marble dust; Glass fiber; Cement mortar; Temperature; Taguchi method; Analysis of varience (ANOVA)